Alcohol Related Toxic Optic Neuropathy Case Series - , Khalid I. Talpur, Sajjad Ali Surhio, Shahzad Memon, Muhammad Memon, Noor Bakht Nizamani (Pakistan Journal of Ophthalmology, 2018)
Purpose: To report a case series of alcohol induced toxic optic neuropathy, discussing their visual status and optic disc changes in response to high dose steroid treatment. Material and Methods: This study was conducted at the Department of Ophthalmology, Liaquat University of Medical and Health Sciences, Hyderabad, Pakistan. Ten cases (twenty eyes) of alcohol induced toxic optic neuropathy were received between November 2009 and January 2010, with chief complaint of sudden loss of vision following use of alcohol. Patients were started with intravenous high dose steroids and vitamin B complex. They were followed up until 3 months for visual improvement and changes of optic disc with the help of fundus photographs. Results: All the patients were males and habitual drinkers with definite history of consuming adulterated alcohol. Seven of the patients were received in first week for acute visual loss while remaining three after 4 weeks. Seventy percent patients responded well to high dose steroid therapy with visual acuity improving from perception of light to 6/6 within 3 months. Conclusion: High dose steroids had a great therapeutic effect on the visual outcome in patients of alcohol induced toxic optic neuropathy. However the optic disc appearance was not proportionate to the visual status of the patients.